Zarwanica – Missionary Marian Pilgrimage Center in the Greek-Orthodox Church in Ukraine - Kordonskyy, Roman; Mączka, Ewelina (Studia Warmińskie, 2014)
In the article an attempt was undertaken to present the phenomenon of Zarwanica (Ukraine) as a holy place, which is a very important Marian veneration center in the Greek-Orthodox Church. Attention should be paid to the fact that pilgrimage centers constitute a huge spiritual value within folk piety and the whole church community. The typical background for the folk piety is the existence of such a holy place which is the basis for the pilgrimage movement, prayer and spiritual reflection. In the first part of the thesis we get informed of the best known places like that in Ukraine. In the second part, the terminology and the history of pilgrimages, including their theological aspect is provided. In the third, Zarwanica is described in its historical and religious setting. The aim of the article is to present Zarwanica as a place, in which “the truth” is the focal point of several levels: the history of the Ukrainian nation, history of spiritual and material culture, art, and above all history of faith, religion, and spirituality. Pilgrims arriving at this holy place can feel the centuries-old history and God’s presence. Zarwanica is the meeting place of thousand of Christians representing the Eastern rite, yet not only them. Publishing the knowledge of Zarwanica aims at making this place popular with Orthodox Church believers, also because of miracles that have happened here, which are officially recognized by the Church, and where people can experience spiritual enrichment.